Childbirth preferences and related fears - comparison between Norway and Israel - Heidi Preis; Yael Benyamini; Malin Eberhard-Gran; Susan Garthus-Niegel (BMC Pregnancy and Childbirth, 2018)
Abstract Background Fear of childbirth (FOC) could have significant impact on women’s childbearing choices and experience. Culture affects the way women conceptualize childbirth, influencing the fears and expectations they may hold in relation to it. In the current study, we examined differences in childbirth preferences of cesarean section and use of epidural analgesia between Norwegian and Israeli pregnant women. Later, we used the Norwegian six-factor solution of the widely-used Wijma Delivery Expectancy Questionnaire (W-DEQ-A) to compare levels of the different FOC factors. Finally, we investigated differences in the associations between FOC and childbirth preferences between the two countries. Methods Secondary analysis of two large surveys. Women from Israel (n = 490) and Norway (n = 2918) were recruited during prenatal check-ups in community clinics and a university hospital. At around 32 weeks of gestation, all participants filled out questionnaires, including the W-DEQ-A. Statistical analysis included exploratory factor analysis, confirmatory factor analysis, M/ANOVA, Spearman’s Rho and Fisher’s Z tests for the significance of the difference between independent correlations. Results The Norwegian six-factor solution of the W-DEQ fit well with the Israeli data. Norwegian women were more concerned about loneliness, feeling less self-efficacy, negatively appraising birth, and lacking positive anticipation. Israeli women were more concerned about negative outcomes for the child and experienced greater general fear and fear of pain. Norwegian women preferred more cesarean sections compared to Israeli women, who preferred more epidural use than Norwegians. FOC factors were more strongly related to childbirth preferences among Norwegians. Conclusions Cultural differences between Israel and Norway are reflected by the differences seen in the levels of fear reported across the six factors. In Israel, birth culture is very medicalized, motherhood is highly revered, and there is an emphasis on having “perfect babies”. In contrast, Norwegian women have fewer children, and birth is considered more natural. This could explain why Israeli women were more concerned that their child might be harmed during birth, while Norwegian women were more concerned with the physical and emotional expectations of birth.